Pengendalian Kualitas Semen PCC di PT Semen Bosowa Banyuwangi Menggunakan Maximum Half-Normal Multivariate Control Chart (Max-Half-Mchart) - Loka, I Melda Puspita; Khusna, Hidayatul; Aksioma, Diaz Fitra (Inferensi, 2024)
Cement is a building adhesive material produced from clinker and has the main ingredients in the form of calcium silicate and additional gypsum. The Indonesian Cement Association (ASI) states that there will be an increase in domestic cement consumption by 5.5% in 2021. Competition in the industrial sector is quite tight, causing PT Semen Bosowa Banyuwangi maintain and improve the quality of its products continuously. One of the steps taken is to check for blaine, residual, and free lime through the laboratory before the cement is distributed. Since there are more than one quality characteristic of Portland Composite Cement (PCC) and each quality characteristic is monitored every shift, the control chart used is a multivariate control chart for individual observations in the form of a Max-Half-Mchart. The Max-Half-Mchart for individual observation can effectively monitor mean and process variability simultaneously. PCC cement quality control using the Max-Half-Mchart in phase I showed that the process was statistically controlled. In phase II, there were out of control observations identified as a shift in the average process. The multivariate process capability measurement results obtained a 〖MC〗_pk value of 1.053, which means that the overall production of PCC cement complies with company regulations.